Descriptive Study of Balanced Nutrition Knowledge, Eating Patterns, and Nutritional Status Among Grade X Students at State Senior High School 22 Surabaya - Ghina Handayani; Ani Intiyati; Inne Soesanti; Dian Shofiya (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Adolescents are prone to nutritional problems due to limited knowledge and unhealthy eating behaviors. This study aimed to describe the balanced nutrition knowledge, dietary habits, and nutritional status of Grade X students at SMA Negeri 22 Surabaya as a basis for promotive and preventive strategies. A descriptive study was conducted involving 79 students selected through proportional simple random sampling. Data were collected using a validated nutrition knowledge questionnaire, SQ-FFQ, and anthropometric measurements, then analyzed descriptively. Most participants were female (70.9%) and aged 16 years (68.4%). A total of 67.1% had good knowledge of balanced nutrition. However, only 43% had normal energy intake. Good dietary diversity was found in 35.4%, and 54.4% had adequate meal frequency. Despite this, 57% had poor overall eating patterns. In terms of nutritional status, 65.8% were within the normal range, 13.9% were undernourished, and 20.3% were overweight or obese. The findings show a gap between knowledge and practice, where good nutritional knowledge does not always translate into healthy dietary behavior. Therefore, targeted interventions are needed to improve adolescents' eating patterns and prevent future nutritional problems.